Two new registered table grape varieties - Hajdu, E.; Ésik, É. (International Journal of Horticultural Science, 2001)
Two table grape varieties — Kósa and Narancsízű — were registered of the hybrids bred in the Research Institute for Viticulture and Enology in I lungary. Both varieties ripe early and are much in demand for the attractive clusters and flavours. As they are hybrids of Vitis vinifera they require similar growing conditions. In the same time with their qualification the two varieties are included in the variety list and allowed to be propagated.